Metformin in Patients With COVID-19: A Systematic Review and Meta-Analysis - Li, Yin; Yang, Xue; Yan, Peijing; Sun, Tong; Zeng, Zhi; Li, Sheyu (Frontiers in Medicine, 2021)
Importance/Background: The coronavirus disease (COVID‐19) pandemic is a critical public health issue. Evidence has shown that metformin favorably influences COVID-19 outcomes. This study aimed to assess the benefits and risks of metformin in COVID-19 patients. Methods: We searched the PubMed, Embase, Cochrane Library, and Chinese Biomedical Literature Database from inception to February 18, 2021. Observational studies assessing the association between metformin use and the outcomes of COVID-19 patients were included. The primary outcome was mortality, and the secondary outcomes included intubation, deterioration, and hospitalization. Random-effects weighted models were used to pool the specific effect sizes. Subgroup analyses were conducted by stratifying the meta-analysis by region, diabetic status, the adoption of multivariate model, age, risk of bias, and timing for adding metformin. Results: We identified 28 studies with 2,910,462 participants. Meta-analysis of 19 studies showed that metformin is associated with 34% lower COVID-19 mortality (odds ratio [OR], 0.66; 95% confidence interval [CI], 0.56 to 0.78; I2=67.9%) and 27% lower hospitalization rate (pooled OR, 0.73; 95% CI, 0.53 to 1.00; I2=16.8%). However, we did not identify any subgroup effects. The meta-analysis did not identify statistically significant association between metformin and intubation and deterioration of COVID-19(OR, 0.94; 95% CI, 0.77 to 1.16; I2=0.0% for intubation and OR, 2.04; 95% CI, 0.65 to 6.34; I2=79.4% for deterioration of COVID-19), respectively. Conclusions: Metformin use among COVID-19 patients was associated with a reduced risk of mortality and hospitalization. Our findings suggest a relative benefit for metformin use in nursing home and hospitalized COVID-19 patients. However, randomized controlled trials are warranted to confirm the association between metformin use and COVID-19 outcomes.